Cybercrime as Threat of National Security of Russia - O. I. Lepeshkina (Теоретическая и прикладная юриспруденция)
The aim of this article is determination of main lines on rise efficacy of anti-cybercrime in Russia. This article describes the Russian law base and international law acts about anti-cybercrime, and also norms of project of Convention United Nations Countering the use of information and communications technologies for criminal purposes, which Russia sent to United Nations in 30 July of 2021.There are the terms “cybercrime”, “cyberspace”, “cybersecurity” in according with international standards of International Organization for Standardization and International Telecommunication Union in this article. There is classification of cybercrimes in this article, which is in criminal law theory.The author makes proposals of main lines of national politics in sphere of anti-cybercrime.